2017
DOI: 10.1016/j.jpain.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Morphine Administration Induces TRPM8-Dependent Cold Hyperalgesia

Abstract: It is not uncommon for patients chronically treated with opioids to exhibit opioid induced hyperalgesia (OIH), and this has been widely reported both clinically and experimentally. The molecular substrate for this hyperalgesia is multifaceted, and associated with a complex neural reorganization even in the periphery. For instance, we have recently shown that chronic morphine-induced heat hyperalgesia is associated with an increased expression of GluN2B containing N-methyl-D-aspartate (NMDA) receptors, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 102 publications
0
20
2
Order By: Relevance
“…Shapovalov et al found a distinct mechanism of TRPM8 regulation in rat DRG neurons with morphine administration leading to an increase in TRPM8 internalization [18]. In contrast to what was reported by Gong et al [19] we did not observe an increase in TRPM8 mRNA expression in response to morphine. In addition, assessment of plasma membrane biotinylated fraction did not reveal an alteration in TRPM8 surface expression.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Shapovalov et al found a distinct mechanism of TRPM8 regulation in rat DRG neurons with morphine administration leading to an increase in TRPM8 internalization [18]. In contrast to what was reported by Gong et al [19] we did not observe an increase in TRPM8 mRNA expression in response to morphine. In addition, assessment of plasma membrane biotinylated fraction did not reveal an alteration in TRPM8 surface expression.…”
Section: Discussioncontrasting
confidence: 99%
“…The activity of the thermosensor TRPM8 in primary sensory neurons is unique in that it senses cool temperatures but also mediates cold-induced analgesia [10][11][12]. TRPM8 was previously found to be involved in the development of cold hyperalgesia following chronic morphine administration, although the underlying mechanisms of this effect involved an upregulation of the channel expression [19]. Shapovalov et al found a distinct mechanism of TRPM8 regulation in rat DRG neurons with morphine administration leading to an increase in TRPM8 internalization [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two hours before menthol administration, rats were subjected to an intraperitoneal administration of a selective TRPM8 antagonist RQ-00203078 (purchased from Tocris Biosicence, United Kingdom) at 0, 0.3, and 3 mg/kg (dissolved in DMSO and then diluted with deionized water) in a within-subject Latin square design. These dose were selected based on the fact that in rats the ED50 value of RQ-00203078 via oral administration is 0.65 mg/kg and that RQ-00203078 at 3 mg/kg dose via intraperitoneal administration produced a profound TRPM8-blocking effect (Gong and Jasmin, 2017; Ohmi et a., 2014). To guarantee the extinction baseline before each test sessions, two extinction sessions were conducted between test sessions.…”
Section: Methodsmentioning
confidence: 99%
“…We also found that prolonged activation of MOR by The activity of the thermosensor TRPM8 in primary sensory neurons is unique in that it senses cool temperatures but also mediates cold-induced analgesia 10−12 . TRPM8 was previously found to be involved in the development of cold hyperalgesia following chronic morphine administration, although the underlying mechanisms of this effect involved an upregulation of the channel expression 19 .…”
Section: Discussionmentioning
confidence: 99%